COVID-19 pandemic: scenario of the Brazilian health system for coping with the crisis (Research, Society and Development, 2020)
Aims: This study aims to describe and analyze the operational capacity of Brazilian states to face COVID-19. Methodology: Data about the number of physicians (intensivists and pulmonologists), ICU beds and respirators in each federal unit in the country were assessed, and then the relationship between the supply of these factors and regional demands was assessed. The disease lethality rate was calculated fifteen days after the first death was recorded by COVID-19, relating it to the regional capacity to manage with the pandemic. Results: It was evident that there are discrepancies in the supply of doctors, ICU beds and mechanical ventilators in order to attend the regional demands arising from the pandemic. The Federal District stands out as the federative unit with the best ratio of doctors and hospital equipment to face the crisis, while states in the North and Northeast in general have relations worse than the national averages. This unequal distribution seems to interfere in the condition of managing with the disease with the possibility of impacting the mortality rates by COVID-19. Conclusion: There is a discrepancy in the availability of human resources and medical equipment in the country suggesting an unequal capacity to face the crisis that can impact the lethality rates by COVID-19 and the collapse of the health system.